Avatar: the last airbender - the rift, part two ebook - Yang, Gene Luen (Avatar: The Last Airbender,, 2015)
Team Avatar find themselves up to their necks in trouble as mysterious forces threaten to destroy land once sacred to the Airbenders! While Aang journeys to the spirit world in search of clues, Toph faces off against her own past! * The official continuation of Airbender from its creators, Michael Dante DiMartino and Bryan Konietzko! * Avatar: The Last Airbender—The Search continues to top the sales charts! * The perfect companion to The Legend of Korra !